Is Aesthetic Dermatology in Unsafe Hands? - Mohan Bhusal; Deeptara Pathak Thapa (Nepal Journal of Dermatology, Venereology & Leprology)
Aesthetic Dermatology is one of the growing subspecialities that involves noninvasive to minimally invasive cosmetic procedures. It has overlapping scope with Aestheticians, Beauticians, and Non-Dermatologist medical practitioners, adding ambiguity and ethical issues. There have been global reports of invasive procedures done by Beauticians and Aestheticians leading to complications like scalp burn, infection and stroke which later led to development of guidelines in different countries. There is a strong need to develop similar guidelines in Nepal in collaboration with different stakeholders. Also, it is equally important to create public awareness so that public will be better informed about whom to consult for their skin concerns, and if needed report to governing bodies regarding negligence.